Simulation of I-V Characteristics of Si Diode at Difference Operating Temperature:Effect of Ionized Impurity Scattering - Siti Lailatul Arofah; Endhah Purwandari; Edy Supriyanto (UNEJ e-Proceeding, 2016)
The usage quality of Si Diode was influenced by the operating temperature. The increment of temperature caused the increased number of ionized impurities. Coulomb interaction between the impurities and the local charge carrier caused the scattering on the impurity. Furthermore, this scattering causes changes in the velocity and mobility of charge carriers. This gives an effect on the distribution of charge carriers, causing changes in the diffusion current density. In this paper, we perform the I-V characteristic of Si diode, simulated in two dimensional structure. Several temperatures (200K-473K) and also the charge carrier mobility were observed as the input parameter of the equation modelled. The simulation results show that the value of current density diffusion of Si Diodes was maximum at temperature of 200K and decreasing at a higher temperature of 473K.